COLOR CHANGES OF DIFFERENT CAD/CAM CERAMIC BLOCKS AFTER IMMERSION IN USUAL BEVERAGES - Ioana Pîrvulescu; Codruța Ille; Raul Rotar; Luciana Goguță; Laura Cîrligeriu; Anca Jivănescu (Romanian Society of Oral Rehabilitation, 2021)
The objective of this study was to verify the color stability after immersion of leucitic, feldspathic, and disilicate ceramic blocks, which are used for chairside CAD/CAM restorations, in frequently used beverages. A total of 48 ceramic discs were made from leucitic, feldspathic, and lithium disilicate ceramic blocks. The discs were divided into four subgroups and immersed in different solutions for 4 weeks: distilled water for control, green tea, coffee, and red wine. A dental spectrophotometer was used to determine the color parameters, and the measurements were obtained during the initial stage, 2 weeks after immersion, and after 4 weeks. The color changes, compared to the reference values, were analyzed by calculating ΔE00. The results of this study revealed that all materials exhibited color changes after immersion in red wine, which slightly exceeded the perceptibility and acceptability threshold. The most significant color changes were observed after immersion in coffee, especially for the feldspathic CAD/CAM ceramic blocks. Within the limitations of this study, it can be concluded that the usual beverages may affect the color stability of the CAD/CAM ceramic blocks, which can compromise the esthetics of the restorations.